Quem veio hoje? : percepção de idosos residentes de Instituições de Longa Permanência (ILP) sobre as atividades assistidas com animais - Schutz, Karina Laux (2020)
The present dissertation aims to identify as appreciations of activities assisted by animals (AAAs) in elderly residents in long-term care institutions for the elderly (ILPIs). For that, a selection of residents was made that registered the research through the Mini-Mental State Examination. Those selected (7 women and 3 men, aged between 64 and 89 years old) answered a sociodemographic questionnaire and a semi-structured interview, with questions about the recovery of the insertion of animals in the institution, the feelings / emotions generated by the interaction and preference for animals selected (including this study: dog, bird and rabbit). This investigation describes as a complementary qualitative and quantitative approach and used by the Content Analysis technique (BARDIN, 2016) for processing data from interviews and field diaries. Five categories were found that emerged from the statements of the elderly participants in the study. They are: "affection", "memories", "importance", "preference for a certain animal" and "fear". This research was able to describe, through the speeches of the participants, the participation and feelings aroused by the elderly residents of ILPIs, through activities carried out with animals inside the places. Equally, a pertinence of this investigation is justified by demonstrating the negative effects of this activity for LTCFs, highlighting the importance of a trained professional and appropriately selected animals.